Immunity to change : how to overcome it and unlock potential in yourself and your organization - Kegan, Robert; Lahey, Lisa Laskow, 1955- (Boston, Mass. : Harvard Business Press, 2009)
"In Immunity to Change, authors Robert Kegan and Lisa Lahey show how our individual beliefs - along with the collective mindsets in our organizations - combine to create a natural but powerful immunity to change. By revealing how this mechanism holds us back, Kegan and Lahey give us the keys to unlock our potential and finally move forward. And by pinpointing and uprooting our own immunities to change, we can bring our organizations forward with us." "This persuasive and practical book, filled with hands-on diagnostics and compelling case studies, delivers the tools you need to overcome the forces of inertia and transform your life and your work."--BOOK JACKET
Pt. I. Uncovering a hidden dynamic in the challenge of change -- 1. Reconceiving the challenge of change -- 2. Uncovering the immunity to change -- 3. "We never had a language for it" : engaging the emotional life of the organization -- Pt. II. Overcoming the immunity to change in organizations, individuals, and teams -- 4. Overcoming the groupwide immunity to change : a Collective approach -- 5. David doesn't delegate : overcoming an individual's immunity to change -- 6. Cathy can't contain herself : overcoming an individual's immunity to change -- 7. The case of Nascent Pharmaceuticals : overcoming individual immunities to help a team succeed -- Pt. III. Over to you : diagnosing and overcoming immunities in yourself and your organization -- 8. Unlocking potential : three necessary ingredients -- 9. Diagnosing your own immunity to change -- 10. Overcoming your immunity to change -- 11. Surfacing your collective immunity to change -- Conclusion : growing your own : how to lead so people develop
Includes bibliographical references (p. [325]-328) and index
Keywords: Organizational change; Change (Psychology); Organizational behavior; Organizational effectiveness; Organizational Innovation; Efficiency, Organizational; Leadership; Psychology, Industrial